What's Yours is Now Mine: Deviant Consumption through Acquisitive Crime. (April 2013) - Martin, Kelly D.; Cullen, John B.; Martin, Michael W.
Deviant consumption in the form of acquisitive crime, or the theft of material possessions by one person from another person or household, is prevalent in countries across the globe. Anomie theory provides a multilevel framework for understanding this prevalent and damaging form of consumer misbehavior, highlighting the societal factors propagating it. The authors conduct a multilevel study that analyzes reports from more than 58, 000 households in 26 countries worldwide. Using hierarchical generalized linear modeling, they contrast household-level crime reports with country data on inequality and cultural values. The findings reveal that wealth inequality, achievement orientation, individualism, future orientation, and uncertainty—both individually and in combination—influence acquisitive crime prevalence. In particular, greater societal wealth inequality increases the positive effects of achievement orientation and uncertainty to promote acquisitive crime. The negative effects of a low future orientation in promoting acquisitive crime are also enhanced under greater inequality. The findings suggest public policy implications at both societal and individual household levels of analysis. Specifically, policies directed at underground markets coupled with consumption adequacy efforts may prove effective in curbing acquisitive crime.